Atlas of the Second World War - Edited by Young, Peter Brig. (Rawalpindi Army Education Publishng House, 1973)
A fully comprehensive guide to the Second World War: theatre by theatre, campaign by campaign, battle by battle. 215 detailed maps cover every aspect of military operations by land sea and air from 1939 to 1945..
Include Illustration, Map and Index
Keywords: World War (1939-1945) -- Military campaigns -- Atlases, British